Exhibition Reviews. Issue 1 (1st June 2018) - Jump, Sophie; Downer-Mellini, Stephanie; Collett, Emily; Brayshaw, Emily; Carriger, Michelle Liu; Hamilton, Caroline; Ferrero-Regis, Tiziana
Caspar Neher: An Exhibition of Set and Costume Designs, Abbott and Holder, London, 23 March–22 April 2017Costumi da Star, Villa Pignatelli Museum, Naples, Italy, 6 June–10 July 2017World Stage Design 2017: Professional and Emerging Costume Design Exhibition Entries, Kuandu Museum of Fine Arts, Taipei, 1–9 July 2017Million Dollar Mermaid: Annette Kellerman, Museum of Arts and Applied Sciences, Sydney, Australia, 10 August 2016–21 January 201811th Annual Emmy Costume Exhibition, FIDM, Los Angeles, CA, 22 August–7 October 2017Chagall: Fantasies for the Stage, LACMA, Resnick Pavilion, Los Angeles, CA, 31 July 2017–7 January 2018The Costume Designer: Edith Head and Hollywood, Bendigo Art Gallery, Bendigo, 29 September 2017–29 January 2018